An Analysis of Abbreviations in Technology as Found in Kompas.com - Dedi Yusuf; Leni Marlina (Universitas Negeri Padang, 2020)
The use of abbreviation is often used in news writing in order to conserve the news space to the readers. So that abbreviation can make the news become clearer, simple and easy to understand by the readers. Abbreviation can be found easily whether it in newspaper or on website such as KOMPAS.com. This research is aimed to figure out the types of abbreviation on KOMPAS.com website especially at technology section. The source of the data of this research is news-text in Bahasa Indonesia which from KOMPAS.com website, at technology section especially at gadget and hardware sections, which is issued on 1st January 2017 until 30th December 2018. This research uses descriptive method. The data analysis is done based on abbreviation theory which is stated by three experts Schendl (2001), Weakly (2006), Andrew (2007). According to them, there are 6 abbreviation types that are acronym (an abbreviation which comes from the combination of the initial letters of every word), contraction (an abbreviation which comes from the combination of the initial and suffix letters from one word), shortening word (an abbreviation which comes by eliminating suffix of one word), clipping word (an abbreviation which comes by eliminating some parts of initial or suffix of one word), initialism (an abbreviation which comes by taking the initial letter of one word), blend (an abbreviation which comes by the result of 2 abbreviations combined). The result of this research shows that there are 6 types of abbreviation on KOMPAS.com especially at technology section: acronym (23%), contraction (2%), shortening word (2%), clipping word (2%), initialism (70%), blend (1%). So, it can be concluded that intialism is the most dominated abbreviation type on KOMPAS.com especially at the technology section, while another dominated abbreviation type found even it is less from 25% is acronym. While the most rarely found abbreviation types on this website are contraction, shortening, clipping word and blend.